NEUROGENIC DYSFUNCTION OF THE LOWER URINARY TRACT: CONSTRUCTION AND VALIDATION OF AN INSTRUMENT FOR NURSING CONSULTATION (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To construct and validate the content of a data collection instrument for the nursing consultation of people with neurogenic lower urinary tract dysfunction in outpatient follow-up. Methods: This is amethodological study composed of two stages: elaboration of the instrument and content validation. Through the search for scientific evidence found in the literature, an instrument for admission consultation wasdeveloped. The content was validated in August 2021 by experts through independent reviews. Results: After the evaluation performed, some modifications were necessary for better adaptation and final presentation of the instrument developed. In the content analysis, 62 items with mean content validity reason below 0.78 were identified, which were excluded from the instrument. The final instrument had 160 items organized into three parts. Conclusion: The instrument represents a guide for the nursing consultation and for futureinvestigations, contributing to the improvement of the quality of care, through the systematization of care and a comprehensive approach to care for this clientele.